Analysis Of Operational Management Of Logistics Services In Improving Employee Performance At CV. Kirana Cahaya Sejahtera Gunungsitoli - Yulisman Laia; Kurniawan Sarototonafo Zai; Yupiter Mendrofa; Maria Magdalena Bate'e (UNIVED Press, 2025)
The purpose of this study is to determine how operational management of logistics services improves employee performance at CV. Kirana Cahaya Sejahtera Gunungsitoli. So the research approach used in this study is to use a qualitative approach. In conducting this research, the researcher has selected and determined the research location as an object that is a source of data and information according to the circumstances and conditions experienced. The location of the research was carried out at CV. Kirana Cahaya Sejahtera Gunungsitoli, which is located at Jln. Gomo, Pasar Gunungsitoli Village, Gunungsitoli District, Gunungsitoli City. So the key information in this study is 10 employees. The researcher uses primary data and data collection techniques in this study using observation, interviews and documentation. And the data analysis techniques used by researchers are data collection, data reduction, data presentation, and drawing conclusions. From the results of the study, it was obtained that the Company's efforts to Improve the Efficiency of Company Performance in operating the company's performance in an effort to improve the efficiency of the company's performance, the company strives to improve deficiencies and always strives to prioritize good service and an easy ordering process for customers, starting from the service of the products owned, easy ordering process, prices offered, strategic location of the company, timely delivery and easy marketing system.